1991
DOI: 10.1093/ajcp/96.6.704
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical Progesterone Receptor Assay: Measurement by Image Analysis

Abstract: To determine the efficiency of image analysis in immunohistochemical progesterone receptor (PgR) measurement, 94 primary breast carcinoma tissue samples were evaluated for PgR by biochemical dextran-coated charcoal assay (DCC) and an immunohistochemical method. Frozen sections immunostained for PgR with a monoclonal antibody (Abbott PgR-ICA, Chicago, IL) and the peroxidase-antiperoxidase technique were scored semiquantitatively histologic score by microscopy and quantitatively (percentage nuclear area immunopo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

2
7
0
1

Year Published

1992
1992
2004
2004

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 21 publications
(10 citation statements)
references
References 0 publications
2
7
0
1
Order By: Relevance
“…Indeed, the correlations for ER and PR are similar to those previously reported for diverse image analysis systems (Sklarew et al 1990;Baddoura et al 1991;el-Badawy et al 1991;Esteban et al 1991Esteban et al , 1994aWong et al 1991;Auger et al 1993;Miller et al 1993). Discrepancies between immunocytochemical and biochemical studies have been ascribed to sampling error and to the inability of the biochemical techniques to differentiate between neoplastic and non-neoplastic breast epithelium.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…Indeed, the correlations for ER and PR are similar to those previously reported for diverse image analysis systems (Sklarew et al 1990;Baddoura et al 1991;el-Badawy et al 1991;Esteban et al 1991Esteban et al , 1994aWong et al 1991;Auger et al 1993;Miller et al 1993). Discrepancies between immunocytochemical and biochemical studies have been ascribed to sampling error and to the inability of the biochemical techniques to differentiate between neoplastic and non-neoplastic breast epithelium.…”
Section: Discussionsupporting
confidence: 78%
“…Today, the determination of estrogen receptor (ER) and progesterone receptor (PR) expression by immunocytochemistry is widely accepted (Allred 1993;Battifora et al 1993;Esteban et al 1994a). This method has been thoroughly evaluated, compared to the previously used dextran-coated charcoal technique of receptor quantification (DeSombre et al 1986;Sklarew et al 1990;Baddoura et al 1991;el-Badawy et al 1991;Esteban et al 1991Esteban et al ,1994aWong et al 1991;Allred 1993;Auger et al 1993;Miller et al 1993;Detre et al 1995), and found to provide equal or better predictive power in terms of prognosis and response to hormone therapy (Pertschuk et al , 1996Reiner et al 1990;Allred 1993a;Esteban et al 1994b;Querzoli et al 1995;Veronese et al 1995). Furthermore, immunocytochemistry is quick, simple, inexpensive, and allows hormone receptor determination even if only small amounts of tumor tissue are available (due to early detection and less invasive techniques, such as needle biopsy or aspiration cytology).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…With refinements in technique and optimal sampling procedures, Esteban et a1 were able to demonstrate a correlation between biochemical methods and immunohistochemical assays of 91.7% (Kappa = 0.74) for ER and 86.7% for PgR (24). Several other studies using computer quantified density measurements of antigen-antibody reaction products for the determination of steroid receptor levels have reported results comparing favorably with the DCC method (25)(26)(27)(28)(29)(30)(31). Both the biochemical and immunologic methods have intrinsic limitations due to sampling and preservation of either immunologic or biochemical reactivity.…”
Section: Discussionsupporting
confidence: 78%
“…Overall survival, however, could not be associated with any image cytometric evaluation, regardless of the cutoffs employed. These results were somewhat surprising because previous studies showed that image analysis is a comparable technique to immunohistochemistry and biochemical assays for ER, as well as correlating well with survival data when used to measure nuclear proliferation markers such as MIB-1 and PCNA (26)(27)(28). PR quantitation by DCC ligand binding biochemical assay showed a statistically significant relationship with both diseasefree and overall survival by univariate analysis and by multivariate analysis with overall survival.…”
Section: Discussionmentioning
confidence: 90%